Ethylene-related gene regulation in rhododendrons under heat stress - Shida Xu; Fanyu Zeng; Xingmin Geng; Lingfeng Mao; Xiaoyue Lin (Horticulture, Environment, and Biotechnology, 2026)

Selenite versus selenium nanoparticles in foliar application: enhancing alfalfa (Medicago sativa L.) and Bacillus subtilis PSL-1 mediated remediation of pyrene-contaminated soil - Hongguan Xie; Lian Gong; Shiwei Lei; Shida Li; Yuxin Feng; Lin Liao; Yue Wang; Kongxi Wang (Environmental Geochemistry and Health, 2025)

Synergistic reduction of air pollutants and carbon dioxide emissions in Shanxi Province, China from 2013 to 2020 - LiLing Wu; Shida Sun; Gaige Zhang; Zimu Jia; Yuyun Liu; Chenxi Xu; Mengjie Guo; Luyao Zhang; Cilan Cai; Runcao Zhang; Jialin Zheng; Wenjie He; et al. (Science of The Total Environment, 2024)

Dynamic Characteristics Analysis of the DI-SO Cylindrical Spur Gear System Based on Meshing Conditions - Yong Zhu; Shida Zhang; Shengnan Tang; Zhengxi Chang; Renyong Lin; Lingbo Zhang (Journal of Marine Science and Engineering, 2024)
The dual-input single-output (DI-SO) cylindrical spur gear system possesses advantages such as high load-carrying capacity, precise transmission, and low energy loss. It is increasingly becoming a core component of power transmission systems in maritime vessels, aerospace, marine engineering, and construction machinery. In practical operation, the stability of the DI-SO cylindrical spur gear system is influenced by complex excitations. These excitations lead to nonlinear vibration, meshing instability, and noise, which affect the performance and reliability of the entire equipment. Hence, the dynamic performance of the DI-SO cylindrical spur gear system is thoroughly investigated in this research. The impact of excitations and nonlinear factors on the dynamic characteristics was investigated comprehensively. A comparative analysis of the gear system was conducted by establishing a bending–torsional coupling vibration analysis model under synchronous and asynchronous meshing conditions. Nonlinear factors such as periodic time-varying meshing stiffness, meshing damping, friction coefficient, friction arms, load sharing ratio, comprehensive transmission error, and backlash were considered in the proposed model. Then, the effect laws of excitations and nonlinear factors such as meshing frequency, driving load fluctuation, backlash, and comprehensive transmission error were analyzed. The results indicate that the dynamic characteristics exhibited staged stable and unstable states under different meshing frequencies and meshing conditions. At the medium-frequency meshing stage (0.96 × 104~1.78 × 104 Hz), alternating phenomena of multi-periodic, quasi-periodic, and chaotic motion states were observed. Moreover, the root mean square value (RMS) of the dynamic transmission error (DTE) in the asynchronized gear system was generally higher than that in the synchronized gear system. It was found that selecting the appropriate meshing condition could effectively reduce the amplitude of the DTE. Additionally, the dynamic performance could be significantly improved by adjusting control parameters such as driving load fluctuation (0~179 N), backlash (0.8 × 10−4~0.9 × 10−4 m), and comprehensive transmission error (7.9 × 10−4~9.4 × 10−4 m). The research results provide a theoretical guidance for the design and optimization of the DI-SO cylindrical spur gear system.

Bioleaching of Silicon from Fly Ash by Co-culture of Silicate Bacteria and Fungi - Yanzhu Lin; Shida Li; Xuefeng Li; Hanrui Lin; Ningfei Lei; Di Wu; Jin Tong; Hongguan Xie (Water, Air, & Soil Pollution, 2023)

Simvastatin-enhanced bioinspired exosome mimetics regulate osteogenesis and angiogenesis for the treatment of glucocorticoid-induced osteonecrosis of the femoral head - Hongyi Jiang; Chao Lou; Liting Jiang; Chihao Lin; Weidan Wang; Zijian Yan; Jiachen Yu; Tingwen Cai; Shida Lin; Jilong Wang; Xiaoyun Pan; Xinghe Xue (Chemical Engineering Journal, 2023)

Evaluating traffic emission control policies based on large-scale and real-time data: A case study in central China - Chao Zou; Lin Wu; Yanan Wang; Shida Sun; Ning Wei; Bin Sun; Jingwei Ni; Jing He; Qijun Zhang; Jianfei Peng; Hongjun Mao (Science of The Total Environment, 2023)